Neuronal cell types in the anterior ventral thalamic nucleus of the camel - Saleh M. Al‐Hussain (14777053) (2023)
The anterior ventral nucleus neurons in of the camel brain were morphologically studied by Golgi impregnation method. Two neuronal types of were found in the camel anterior ventral thalamic nucleus, namely, Golgi-type I neurons and Golgi-type II neurons. Those neurons were generally similar to their counterparts in the human thalamus. The Golgi-type I neurons exhibited medium to large cell body (mean diameter = 25 μm) which was either multipolar or triangular in shape. They had from 3 to 10 primary dendrites with many branches but with no spines or appendages. The Golgi-type II neurons had small to medium size (somatic mean diameter = 17.5 μm), their cell bodies were variable in shape, some were round, and others were multipolar or fusiform. These cells bodies had two to six primary dendrites with few branches that may have spines and/or grape-like appendages. Our findings shed some light on the anterior ventral thalamic nucleus structure of the camel as one of the strongest adaptive mammals to the hard climatic conditions.  Other Information Published in: The Anatomical Record License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ar.24592